Routine use of BACTEC 16B bottles to remove antibacterial and antitumor agents from blood cultures of cancer patients. - Hopfer, R L (1983)
A total of 1,764 paired sets of BACTEC 6B and 16B blood culture bottles were collected from patients for analysis. The majority of the patients were receiving antibiotic therapy at the time the blood specimens were collected. A total of 126 isolates were considered clinically significant. Of these, 58 grew in both 6B and 16B bottles, 25 grew only in 6B bottles, and 43 grew only in 16B bottles. In both bottles, the same amount of time was required to detect a positive culture. In 18 patients, septicemias were detected in the 16B bottles that were not detected in the 6B bottles. In seven patients, microorganisms were detected in the 6B bottles that were not detected in the 16B bottles. Interestingly, the antibiotic therapy was changed for only 4 of the 18 patients whose septicemias were detected only in the 16B bottles. Finally, an in vitro study showed that certain chemotherapeutic agents can cause the inhibition of growth of several microorganisms when tested in 6B bottles. These inhibitory effects were reduced or eliminated when the same organism-drug combinations were tested in 16B bottles.